Analisis korelasi antara pernikahan di usia muda dengan pencegahan maksiat beserta dampaknya - binti mukhlis, auliya zuhrin (Maliki Interdisciplinary Journal, 2025)
Early marriage is often considered as a solution to avoid immoral acts, especially in a society that is very concerned about free association in the modern era. However, early marriage poses various challenges, such as lack of psychological (mental), financial, and life skills readiness, which can affect the welfare and stability of the household. This article shows that early marriage causes various impacts regarding negative psychology, such as stress and anxiety, especially if the individual is not yet mentally mature. In addition, financial dependence on parents can complicate the relationship between young couples and extended families. This phenomenon shows that comprehensive readiness is needed before deciding to marry at a young age so that the marriage can run well. This article highlights the importance of readiness in various aspects to achieve a healthy and harmonious marriage. The phenomenon of early marriage has become a hot topic in society, especially in Indonesia, where strong culture and beliefs influence decisions related to marriage. Many parents feel that early marriage can be a solution to prevent their children from falling into promiscuity and immoral acts. This is especially common in areas that do not prioritize higher education, as well as among graduates of Islamic boarding schools. Getting married at a young age has positive aspects, such as providing certainty of bond and fulfilling religious obligations to abstain from adultery. However, there are many aspects that must be considered before deciding to get married, including mental, psychological, financial readiness, and knowledge in managing a household. This article shows that women who marry at a young age tend to experience various psychological pressures, such as anxiety, stress, and discomfort. This happens because at that age, individuals are usually still in the stage of finding their identity and learning to manage emotions. In addition, lack of financial readiness is also a problem that often arises, especially if the young couple relies on parental support. This dependence can cause conflict in the marriage relationship, especially if parents are too involved in their household problems. This article examines the benefits and challenges of early marriage, and provides a comprehensive perspective on the readiness needed to live a married life at a young age.